1983
DOI: 10.1152/ajprenal.1983.245.1.f32
|View full text |Cite
|
Sign up to set email alerts
|

Autoregulation in vasa recta of the rat kidney

Abstract: Vasa recta blood flow autoregulation was studied by measuring flow velocity in individual vessels on the papilla surface with a video adaptation of the dual-slit erythrocyte velocity method. Vessel diameter did not vary with arterial pressure in the range of 60-150 mmHg, allowing the calculation of the ratio of flows in a single vessel at two pressures from the ratio of velocities. Flow velocity in single vasa recta increased with arterial pressure to 75 mmHg, remained constant in the range of 75-125 mmHg, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
1
1

Year Published

1985
1985
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 0 publications
1
22
1
1
Order By: Relevance
“…This hypothesis is supported by observations, particularly in volume-expanded rats, of poor autoregulation of medullary blood flow (MBF) (13,18,21,28,35,39,40). In contrast, however, other studies have demonstrated efficient autoregulation of MBF in rats and dogs (6,9,17,(23)(24)(25)(26)(27)29), even under conditions of volume expansion (24). These and other observations have led to an alternative hypothesis: that increased RAP increases the renal production of nitric oxide, which in turn mediates the increase in renal interstitial hydrostatic pressure (25).…”
mentioning
confidence: 83%
“…This hypothesis is supported by observations, particularly in volume-expanded rats, of poor autoregulation of medullary blood flow (MBF) (13,18,21,28,35,39,40). In contrast, however, other studies have demonstrated efficient autoregulation of MBF in rats and dogs (6,9,17,(23)(24)(25)(26)(27)29), even under conditions of volume expansion (24). These and other observations have led to an alternative hypothesis: that increased RAP increases the renal production of nitric oxide, which in turn mediates the increase in renal interstitial hydrostatic pressure (25).…”
mentioning
confidence: 83%
“…The results of a recent study, however, cast doubt on this proposal. 16 The purpose of the present investigation was to determine if pressurenatriuresis is associated with changes in medullary hemodynamics or renal interstitial pressure (or both).…”
mentioning
confidence: 99%
“…Previous studies have examined the effects of reducing RPP after pressure was first increased by bilateral carotid occlusion. 10 - 16 Others have studied the effects of elevating RPP by infusion of catecholamines 9 -17 or by ligation of the carotid arteries.…”
mentioning
confidence: 99%
“…32 The reason for the discrepant results is unknown. Papillary blood flow could be altered in the absence of changes in red blood cell velocity if the number of perfused vasa recta capillaries is altered by changes in RPP.…”
mentioning
confidence: 99%